2019
DOI: 10.1002/jocc.12125
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Marijuana Use, Anxiety, and Academic Performance Among College Students

Abstract: This article examines the relationship between marijuana use and anxiety symptoms among college students, with a secondary focus on marijuana use and grade point average (GPA). A secondary analysis was conducted on data obtained from the American College Health Association–National College Health Assessment. Results indicated that marijuana use was negatively associated with GPA among students with current anxiety and no formal treatment. The relationships between these variables may be more complex than previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Literature has emerged which addresses the opinions of all stakeholders on the role of anxiety especially in educational assessments. Most of them affirm that anxiety affects the learner's performance and may influence negative learning outcomes (Owan, Eno & Esuong, 2019;Amini, Amini & Reamen, 2019;Wallis, Gretz, Rings & Eberle, 2019). Previous and recent literatures focus on explaining the concept of test anxiety and its influence on educational outcomes (Trigueros, Padilla, Aguilar-Parra, Rocamora, Morales-Gázquez & López-Liria, 2020;Woldeab & Brothen, 2019;Riyazi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Literature has emerged which addresses the opinions of all stakeholders on the role of anxiety especially in educational assessments. Most of them affirm that anxiety affects the learner's performance and may influence negative learning outcomes (Owan, Eno & Esuong, 2019;Amini, Amini & Reamen, 2019;Wallis, Gretz, Rings & Eberle, 2019). Previous and recent literatures focus on explaining the concept of test anxiety and its influence on educational outcomes (Trigueros, Padilla, Aguilar-Parra, Rocamora, Morales-Gázquez & López-Liria, 2020;Woldeab & Brothen, 2019;Riyazi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While we did not find an association between marijuana use frequency (i.e., number of days marijuana used in the past 7 days) and GPA, our data show that students who answered the question with 'yes' reported lower GPAs compared with students who answered with 'no'. Arria et al (2015) did not find an association between marijuana use and GPA, whereas Meda et al (2017), Suerken et al (2016), Souza, Hamilton & Wright (2019), and Wallis et al (2019 all reported a negative relationship between marijuana use and academic success.…”
Section: Alcohol Smoking and Drugs Consumptionmentioning
confidence: 71%
“…The two most commonly abused substances among college students are alcohol and marijuana ( Meda et al, 2017 ). Both have been shown to be related to decreased academic performance in a number of published studies ( Wallis et al, 2019 ). Drug use is considered a major factor associated with inferior academic success and more frequent alcohol consumption is negatively correlated with GPA ( Arria et al, 2015 ; Conway & DiPlacido, 2015 ; Meda et al, 2017 ; Souza, Hamilton & Wright, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has also been attention in the literature to students’ health as a determinant of performance. Regarding student health and academic performance, Larson et al ( 2016 ) and Wallis et al ( 2019 ) both find strong relationships between GPA and psychological and physical health. Correlates include mental health history and marijuana use.…”
Section: Literaturementioning
confidence: 99%
“…Recent work in economics, educational psychology, and higher education have expanded and refined the list of student-based inputs affecting educational attainment and academic success to include the importance of personality characteristics (Schmitt et al 2009 ; Heckman and Kautz 2012 ; Richardson et al 2012 ; Kautz et al 2014 ; Caviglia-Harris and Maier 2020 ; Sweet et al 2019 ; and Martínez et al 2019 ), peers (Berthelon et al 2019 ; Pu et al 2020 ) and student health (Larson et al 2016 ; and Wallis et al 2019 ). Each of these categories of determinants represent a wide literature covering specific cases from practical intelligence (Schmitt et al 2009 ), grit (Fosnacht et al 2019 ), substance abuse (Wallis et al 2019 ), and stress from financial or family difficulties (Larson et al 2016 ).…”
Section: Literaturementioning
confidence: 99%